2017
DOI: 10.1111/jpc.13559
|View full text |Cite
|
Sign up to set email alerts
|

Adversity and resilience amongst resettling Western Australian paediatric refugees

Abstract: Refugee children have complex backgrounds with exposure to multiple traumatic events. Comprehensive standardised health and psychological screening is recommended to target intervention. Further validation of culturally age-appropriate mental health screening tools in this diverse population is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 32 publications
2
41
0
Order By: Relevance
“…The focus was more a rapid assessment of the problem magnitude in the target population than the individual diagnosis, similar to a study from Sweden, where the usefulness of a self-reporting questionnaire was analysed [ 40 ]. A study from Western Australia recommended the development of longitudinal studies to learn about the connection between previous suffering and the mental health outcome of refugee children [ 41 ]. It has to be kept in mind that the contact time between the physician and the examined URM was very low, and options for follow-up were practically non-existent, also due to a rapid allocation of refugees to different parts of Germany.…”
Section: Discussionmentioning
confidence: 99%
“…The focus was more a rapid assessment of the problem magnitude in the target population than the individual diagnosis, similar to a study from Sweden, where the usefulness of a self-reporting questionnaire was analysed [ 40 ]. A study from Western Australia recommended the development of longitudinal studies to learn about the connection between previous suffering and the mental health outcome of refugee children [ 41 ]. It has to be kept in mind that the contact time between the physician and the examined URM was very low, and options for follow-up were practically non-existent, also due to a rapid allocation of refugees to different parts of Germany.…”
Section: Discussionmentioning
confidence: 99%
“…Referrals for humanitarian entrants and ASs come from medical practitioners, the Humanitarian Entrant Health Service, school or community nurses/psychologists, case workers or via IHMS. Standardised RHS assessment proformas are completed for all new patients using professional interpreters . As previously described, RHS assessments are based on clinical experience, local research and audit and evidence‐based national refugee health screening guidelines .…”
Section: Methodsmentioning
confidence: 99%
“…Hanes et al . used a refugee‐specific tool R‐ACE in their Western Australian paediatric refugee clinic that captured wider refugee ACEs and found that 63% of their clinic population had >3 risks . The modified version of the ACE checklist (Fig.…”
Section: Discussionmentioning
confidence: 99%